The Effects Of Financial performance and Institutional Ownership On The Stock Price of Mining Company In Indonesia Stock Exchange (IDX) Year 2016-2020 - Harinurdin, Erwin (Universitas Serang Raya, 2022)
This study aims to determine how the influence of company financial performance and institutional ownership on stock prices. The population in this study were mining companies listed on the Indonesia Stock Exchange, namely PT Adaro Energy Tbk, PT Aneka Tambang Tbk, and PT Bukit Asam Tbk during the 2016-2020 period. The independent variables in this study are institutional ownership, and financial performance as proxied by Earning Per Share, Price Earning Ratio, Price to Book Value, Dividend Per Share and the dependent variable in the study is stock price. The research sample was taken by purposive sampling method, namely based on 3 predetermined criteria, a sample of 3 companies was obtained. The method of analysis used in this study is multiple regression models. The data used in this study are data taken from the IDX financial statements, especially in the mining industry namely PT Adaro Energy Tbk, PT Aneka Tambang Tbk, and PT Bukit Asam Tbk during the 2016-2020 period. The results of this study indicate that Price Earning Ratio has a positive effect on stock prices. Meanwhile, Earning Per Share, Price to Book Value, Dividend Per Share, and Institutional Ownership have no significant effect on stock prices.